ANALYSIS OF STUDENTS’ MISTAKES IN SOLVING CIRCLE PROBLEM IN CLASS XI MIPA 2 SMAN 1 BANGKINANG KOTA - Miseriyati; Ravina Faradilla Syahril (Jurnal Prinsip Pendidikan Matematika, 2020)
This study aimed to determine student’s mistakes in solving mathematical problems on the circle in SMAN 1 Bangkinang Kota. This research is a qualitative descriptive study. This research subjects consisted of 34 students consisting of 12 boys and 22 girls. The technique of data collection using a written test. The research instrument used was a learning achievement test consisting of 6 items made by the teacher and based on Basic Competency 3.3 analyze circle analytically. Basic Competency 3.3 developed into six Indicators of Competency Achievement. Each item measures different Indicators of Competency Achievement. Student’s answers were analyzed descriptively qualitatively by looking at the type of mistake students made on each item. The result showed that mistakes made by students were fact errors, concept errors, principle errors, and operating errors. The mistakes made by students are caused by students not being careful in solving problems and not understanding the rules of algebraic operations. This research result is the kind mistakes of most students do is operating errors as much as 46,47%; then students do concept errors as much as 33,80%; principle errors as much as 15,49%; and fact errors as much as 4,22%.